Evaluation of groundwater vulnerability to contamination and geochemical characteristics in an alluvial aquifer of Eshtehard plain, Iran - Khodapanah, Leila (2012)
Amajority of the population in Eshtehard district depends upon the availability of quality groundwater from public or private sources. Eshtehard alluvial aquifer is the main source for irrigation, industrial and domestic uses. Recent anthropogenic activities, though, have created a potentially vulnerable environment as groundwater becomes exposed to contamination from municipal, industrial, and agricultural practices threatening the short and long term sustainability of high quality groundwater as a natural resource. Industrial discharge, waste disposal sites,application of pesticidesand fertilizers, poultry farms and municipal sewage are examples of potential source contamination in Eshtehard. Groundwater vulnerability to contamination from surface sources was evaluated for Eshtehard aquifer using a modified GIS based DRASTIC and GOD vulnerability methods. The study also evaluates groundwater quality and hydrochemistry. Chemical compositions of 114 groundwater samples were used to assess the groundwater quality in the study area and to validate the vulnerability mapsproduced by the two mentioned methods above. Most water samples aregrouped into two categories: relatively low mineralizedof Ca–HCO3 type and high mineralizedwaters of Na–Cl type,which indicate the intrusion of saline water and dissolution of carbonate minerals.Based onMANOVA test (P=0.05) on water samples collected during wet and dry seasons didn’t show any significant difference. Concentrations of most of the groundwater quality indicators exceed the maximum allowable limits set by WHO drinking water standards. The chemical analysis also indicates strong affect of anthropogenic activities on the groundwater quality as implied by high nitrate, chloride, and sulfateconcentrations. High levels of salinity and sodium content suggest that the most of groundwater samples are of poor to medium quality for irrigation purposes.The factor analysis reveals that there are two sources of solutes: (1) saline water intrusion with high loading of Cl, Na, Ca, EC, TDS and K; (2) anthropogenic activities, characterizedby high loadings of NO3, SO4 and Mg. For evaluating the groundwater vulnerability in Eshtehard area based on DRASTIC model, two challenging issues were encountered in this study: recharge estimation and alluvial media rating. Direct groundwater recharge from precipitation in semi arid areas is generally small, usually less than about 5% of the average annual precipitation, with a high temporal and spatial variability. A combined groundwater balance and water table fluctuation method was applied to estimate the groundwater recharge in the research area. Original rating tables provide sufficient detail for mapping at theregional scale, where broad ranges of geologic material are present. However,modified rating tables improved spatial representation of input parameters atlocal scales, which is useful for local planning. The DRASTIC and GOD’s index values and maps for Eshtehard alluvial aquifer were generated in GIS environment. The Classic DRASIC was modified and optimized by incorporation of simple statistical and geostatistical techniques for the revision of the factor rating and weighting of all the parameter. The criterionfor these modifications was based on the correlation coefficientof each parameter with the nitrates concentration in groundwater.The correlation coefficient was obtained as r = 0.53, r = 0.42 and r = 0.68 (p< 0.01) for the original DRASTIC, GOD and modified DRASTIC methods, respectively. On the basis of their statistical significance, original ratings and weighting of the parameters werechanged in the DRASTIC equation. Following the above-mentioned modifications,the correlation coefficient between groundwater pollution potential and nitrates concentration was considerably improvedand rose to 15% higher than the original method. The results also showed that both GOD and modified DRASTIC indices values are relatively high and thus Eshtehard aquifer is considered vulnerable to pollution. However, the results indicated that the vulnerability prediction by DRASTIC proved superior to GOD in this particular hydrogeologic setting. These classification of the vulnerability index showed that central and downstream parts of the aquifer are most vulnerable to pollution. The salt flat in north and the alluvial fans of the southern heights yielded moderate scores. The aquifer in and around Eshtehard township, industrial zone and cultivation lands are highly susceptible to contamination.